Impact of aqua drugs and chemicals on the recoveries of fish diseases and total fish production in Sherpur region of Bangladesh (Asian Journal of Medical and Biological Research, 2016)
The present study was conducted to investigate the impact of aqua-drugs and chemicals on fish health and total fish production in Sherpur region, Bangladesh from July 2014 to June 2015. Forty nine different types of aqua-drugs and chemicals were recorded in the study area; among those sixteen types mainly ADDIC drugs and chemicals were widely used by the farmers for treatment of different fish diseases. It was recorded that GR Plus, Active Blue with Copper sulphate, ID Plus, Aqua c vit and H. vit plus were used for the treatment of EUS in Pangus, Shing and Thai koi which had an average recovery of 80-90%. For the treatment of Edwardsiellosis in Pangus and Thai koi, farmers used GR Plus, ID Plus, OTC power, Aqua c vit, H.vit plus and potassium permanganate which had an average recovery of 75-80%, and for the treatment of dropsy in Thai koi and Shing GR Plus, ID Plus, OTC power, Aqua c vit, H.vit plus and potassium permanganate were used which had an average recovery of 75-85%. Histopathology of liver and kidney of fishes were almost normal in control ponds, whereas, in fish organs from drug treated ponds had pathological changes like necrosis, pyknotic cells, hemorrhage, fat droplet, ilets of langerhens, degeneration of kidney tubules and vacuums. Total production of Thai koi, Shing and Pangus was 10,000 kg/acre, 10,000 kg/acre, and 13,000 kg/acre in drugs treated ponds; whereas, such value was 5,000 kg/acre, 4,500 kg/acre and 6,500 kg/acre in non-treaded ponds, respectively in the study areas. In control ponds, mortality rate was comparatively high and production was also low than drugs treated ponds. End of the experiment, it was observed that efficacy of drugs of Aqua Drug and Disease Information Centre (ADDIC) was excellent.Asian J. Med. Biol. Res. December 2015, 1(3): 600-606